Leveraging the CulapCulip YouTube Channel as an Innovative Medium for Islamic Religious Education in Elementary Schools - Nazliyani Pane; Nasrun Salim Siregar (MASI Mandiri Edukasi, 2025)
The development of information and communication technology has provided new opportunities in learning, including in Islamic Education, which often faces challenges in attracting the interest of elementary school students. This research aims to explore the use of the CulapCulip YouTube channel as an innovative medium for PAI learning at SDIT Ummi Aida Medan. The research employs a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects include the school principal, PAI teachers, students, and parents. The research findings show that the utilisation of CulapCulip has a positive impact on students in three main aspects. First, from the motivation aspect, students are more enthusiastic, focused, and eager to participate in lessons due to the short, engaging, and age-appropriate video presentations. Secondly, from the aspect of understanding, students find it easier to comprehend abstract material, such as the stories of the prophets, and are able to retell the core lesson in their own words. Thirdly, from the aspect of religious attitudes, students show more positive behavioural changes, including diligently memorising prayers, emulating honesty, and behaving politely. For teachers, this media facilitates the delivery of material, creates a more interactive classroom atmosphere, and saves teaching time. In addition, the support from school principals and parents emphasises that CulapCulip is not only effective as a learning medium but also relevant in shaping the Islamic character of students. Thus, the use of CulapCulip YouTube can be an alternative strategy for innovative, enjoyable, and contextual PAI learning in facing the challenges of education in the digital era.